2021
DOI: 10.11604/pamj.2021.38.95.15044
|View full text |Cite
|
Sign up to set email alerts
|

Etude de l'incidence des infections nosocomiales et facteurs de risque dans les maternités de la ville de Mbujimayi, République Démocratique du Congo

Abstract: Introduction cette étude vise à déterminer l´incidence des infections nosocomiales et les facteurs de risque chez les accouchées et les nouveau-nés dans les maternités de la ville de Mbujimayi en République Démocratique du Congo. Méthodes il s´agit d´une étude descriptive longitudinale d´incidence et facteurs de risque des infections nosocomiales dans les 231 maternités, qui a été réalisée chez les sujets indemnes de la pathologie au départ qu´on devrait suivre en utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Another study by Rachel et al reported that E. coli was the most prevalent bacteria [21]. Our frequency of urinary infections among women was lower than that reported by Bukasa et al [7], (18% Vs. 37%). However, E. coli was also the most identified bacteria (54.5%) in this study, which is in agreement with our results (62.4%).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Another study by Rachel et al reported that E. coli was the most prevalent bacteria [21]. Our frequency of urinary infections among women was lower than that reported by Bukasa et al [7], (18% Vs. 37%). However, E. coli was also the most identified bacteria (54.5%) in this study, which is in agreement with our results (62.4%).…”
Section: Discussioncontrasting
confidence: 56%
“…This was more pronounced in non-university centers and in medium-sized hospitals. However, a meta-analysis concluded that the pooled prevalence of these nosocomial infections was much higher in developing countries (15.5 per 100 patients) [6,7]. In Morocco, although there are no national legislations that mandate the declaration of all cases of nosocomial infections, the first national survey on nosocomial infections was carried out in 1994 and revealed a prevalence rate of 9%.…”
Section: Introductionmentioning
confidence: 99%